Portugal : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Portugal. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that following robust growth in 2017, driven by investment and exports, activity in Portugal is expected to moderate in 2018. Unemployment continues to fall on the back of sustained employment growth. Credit growth continues to lag the recovery in economic activity, as banks repair their balance sheets. However, rising capital ratios, falling rates of non-performing loans and lower impairments meant that the resilience of banks improved significantly in 2017. Further improvement is expected in 2018. Nevertheless, no significant acceleration in credit growth is expected, and the economy should continue deleveraging its external balance sheet.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet